Improving the estimation of the tuberculosis burden in India - Krycia Cowling; Rakhi Dandona; Lalit Dandona (The World Health Organization, 2014)
Although India is considered to be the country with the greatest tuberculosis burden, estimates of the disease's incidence, prevalence and mortality in India rely on sparse data with substantial uncertainty. The relevant available data are less reliable than those from countries that have recently improved systems for case reporting or recently invested in national surveys of tuberculosis prevalence. We explored ways to improve the estimation of the tuberculosis burden in India. We focused on case notification data - among the most reliable data available - and ways to investigate the associated level of underreporting, as well as the need for a national tuberculosis prevalence survey. We discuss several recent developments - i.e. changes in national policies relating to tuberculosis, World Health Organization guidelines for the investigation of the disease, and a rapid diagnostic test - that should improve data collection for the estimation of the tuberculosis burden in India and elsewhere. We recommend the implementation of an inventory study in India to assess the underreporting of tuberculosis cases, as well as a national survey of tuberculosis prevalence. A national assessment of drug resistance in Indian strains of Mycobacterium tuberculosis should also be considered. The results of such studies will be vital for the accurate monitoring of tuberculosis control efforts in India and globally.